Knowledge, Attitude and Practice among Women Regarding Postnatal Exercises; A Cross-Sectional Study Across Lahore in Private Sector - Rabia Majeed, Samer Zehra, Zaara Furqan, Mamoona Shoukat, Mahnoor Samad, Tayyaba Gulzar, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study is aimed to assess knowledge, attitude and practice among women regarding post-natal exercises. Methodology: A cross sectional study was conducted across private sector in the gynecological and obstetrical department of Punjab Social Security Hospital, Ittefaq Hospital, Hameed Latif Hospital and Khair-un-Nisa Hospital. Through non-probability convenient sampling, 120 postpartum mothers were chosen. A structured questionnaire was used to collect socio-demographic and gynecological data, as well as to assess knowledge, attitude, and practice regarding PNE. Married females of ages 18-40 were included and females with postpartum hemorrhage and active infection/sepsis were excluded from the study. An informed consent was taken from the study participants. SPSS 25 was used for data analysis. Results: 53.3% had lower segment caesarian section. Breathing exercises were the most common type of exercise among participants (51.7%).74.2% believed that uterine prolapse can be prevented through PNE.99.2% of the study population agreed that PNE is necessary while 81.7% felt guilty on omitting PNE. For 50% of participants, Household work was the most common barrier in performing PNE. Conclusion: There was significant correlation between knowledge, attitude and practice. More than half of the participants had knowledge (mean score=4.116) about PNE but they were not fully aware of its potential benefits and lack adherence. It is important to create awareness and educate people about the postnatal exercises so that postpartum dysfunctions can be prevented and women health can be improved.